Use of an Extract from a Scenedesmaceae Microalgal Isolate in Polyurethane-Based Composite Films: A Preliminary Evaluation from Environmental and Public Health Perspectives - İrem Nur Kazan; Selin Doğan; Medine Güllüce (JOURNAL OF BIOTECHNOLOGY AND STRATEGIC HEALTH RESEARCH, 2026)
Objective: Plastic production, use, and degradation are increasingly important public health concerns because of environmental pollution, microplastic formation, and human exposure. Healthcare packaging, personal protective equipment, and single-use products also contribute to plastic waste. This study investigated the use of a chloroform extract from a microalgal isolate morphologically consistent with Scenedesmaceae as a biological additive in a polyurethane (PU) matrix.Methods: Microalgae were isolated on BG11 agar and morphologically pre-identified by light microscopy according to cell shape, coenobial organization, and cell number. Dried biomass was extracted with chloroform, and the extract was incorporated into PU at 10%, 20%, and 40% on a dry-matter basis. Neat PU served as the control. Three independently prepared films per formulation were evaluated for physical properties, water absorption, and weight loss after 7, 15, and 30 days of soil burial.Results: Increasing extract content reduced flexibility and increased brittleness. Water absorption was 41.70±0.53%, 56.81±1.45%, 54.03±1.24%, and 104.66±1.81% in neat PU, 10%, 20%, and 40% Alg/PU films, respectively. After 30 days, weight loss was 16.23±0.45%, 19.86±0.45%, 21.30±0.47%, and 26.78±0.58%, respectively, showing a descriptive increasing trend with extract content.Conclusion: Microalgal extract incorporation increased water absorption and soil-burial weight loss, while high loading impaired film homogeneity, flexibility, and physical integrity. Among the tested formulations, the 10% Alg/PU film retained comparatively better flexibility and homogeneity. These findings support further mechanical, structural, barrier, and biodegradation studies of biologically modified PU composites.